The Doctrinal Rooting of the Theory of "The End Justifies the Means" - Isteti, Mohammad Sharif Mustafa; Al-Tamimi, Emad Mohammad Reda Ali; Al-Kurdi, Raed Ali Mohammad (Dirasat: Shari'a and Law Sciences, 2020)
The study dealt with the issue of the rule "the end justifies the means" to show the extent to which this rule is in agreement or inconsistent with Islamic Sharia. The study came in two sections. In the first topic, it defined the rule by first defining its vocabulary, then defining it as a compound term, and clarifying the origin and source of this rule. The study showed the position of Islamic law on the rule. In the second topic, the study mentioned practical examples of Islamic law to show the points of agreement and disagreement with the rule. To achieve the study objectives, the inductive method was used by tracking the sayings of ancient and contemporary jurists, then analyzing these sayings and doctrines by presenting them to the Sharia and the legislation. The study concluded that ends influence their means. Accordingly, the rule "the end justifies the means", regardless of the reason for which it was established, does not absolutely contradict Islamic law. There are many jurisprudential rules and provisions consistent with this rule. The study showed the legal controls that must be met to work with the rule of "the end justifies the means".